Awareness of Drug Addiction among Secondary-Level Students in Nepalgunj, Nepal - Rijal, Nandita; Sharma, Vimla (Academia Research Journal, 2026)
Drug addiction poses a significant public health challenge in Nepal, especially in border areas like Nepalgunj, where accessibility to substances and socioeconomic vulnerabilities increase risks. This study evaluated the level of awareness about drug addiction, its risks, causes, consequences, and prevention measures; among secondary-level students in two schools in Nepalgunj: Mangal Prasad Secondary School (public) and Gyanodaya Vidya Niketan Secondary School (private). A cross-sectional descriptive study was carried out with 300 secondary-level students (150 from each school) using a structured, self-administered questionnaire. Data included sociodemographic details, knowledge of common drugs, health impacts, risk factors (e.g., peer pressure), and prevention strategies. Descriptive statistics and comparative analyses between public and private schools were conducted. Students showed moderate overall awareness: 92% acknowledged drug addiction as harmful to health, yet only 58% demonstrated comprehensive understanding of long-term consequences (e.g., dependence, HIV transmission, academic failure). Peer pressure (85%) and curiosity (72%) were accurately identified as leading causes. Awareness levels were significantly higher in the private school (68% with adequate knowledge) than in the public school (45%; p<0.05), likely influenced by differences in curriculum emphasis and socioeconomic backgrounds. Key knowledge gaps included underestimation of cross-border drug supply and limited familiarity with rehabilitation services. Secondary-level students in Nepalgunj possess moderate but inconsistent awareness of drug addiction, with pronounced gaps in depth and prevention knowledge, especially in public schools. These results underscore the need for tailored school-based awareness initiatives in mid-western Nepal to bridge deficiencies, lower vulnerability among secondary-level students, and support evidence-based national prevention efforts amid escalating substance use.